Associations between hormonal contraception use, sociodemographic factors and mental health: a nationwide, register-based, matched case–control study. Issue 10 (15th October 2020) - Toffol, Elena; But, Anna; Heikinheimo, Oskari; Latvala, Antti; Partonen, Timo; Haukka, Jari
Abstract : Objectives: Sociodemographic and mental health characteristics are associated with contraceptive choices. We aimed to describe the sociodemographic, reproductive and mental health characteristics of all fertile-aged women in Finland who used hormonal contraception (HC) in 2017. Design: A nationwide, register-based study. Setting: All women living in Finland in 2017; data from the Care Register of Health Care, Medical Birth Register, Population Register Centre, Prescription Centre, Register of Induced Abortions. Participants: All women aged 15–49 with one redeemed HC prescription in 2017 (n=294 356), and a same-sized, age-matched and residence-matched, control group of non-users. Outcomes: Rates of HC use; associations between HC use and mental disorders, sociodemographic and reproductive characteristics. Results: 25.8% of women aged 15–49 years used HC. Women with the lowest socioeconomic levels had lower odds of using HC than women with upper-level statuses (OR, 95% CI students: 0.97, 0.94 to 0.99; entitled to pension: 0.66, 0.63 to 0.69; other: 0.87, 0.85 to 0.89; unknown: 0.90, 0.85 to 0.90). Women with the highest education (secondary: 1.46, 1.43 to 1.48; tertiary: 1.64, 1.58 to 1.70; academic: 1.60, 1.56 to 1.63) and income (second quarter: 1.57, 1.54 to 1.60; third quarter: 1.85, 1.82 to 1.89; fourth quarter: 2.01, 1.97 to 2.06), and unmarried women had higher odds of using HC than women with the lowest education and income levels, and married (0.61, 0.60 to 0.62), divorced (0.86, 0.84 to 0.88), widowed (0.73, 0.65 to 0.83) or other marital status women (0.26, 0.22 to 0.30). Parous women (0.70, 0.69 to 0.71), those with previous induced abortion(s) (0.91, 0.89 to 0.92) or recent eating (0.68, 0.62 to 0.75) or personality (0.89, 0.79 to 0.97) disorders had lower odds of HC use. Absolute risk differences between women with and without mental disorders ranged from 3.1% (anxiety disorders) to 10.1% (eating disorders). Conclusions: A quarter of the fertile-aged women use HC in Finland. Sociodemographic disparities persist in relation to HC use, although of small effect size. HC use is less common among women suffering from severe to moderate psychiatric disorders, especially eating disorders.